MALAYSIA STROKE CONFERENCE 2022 2: E-Poster Presentation - 2022, Malaysia Stroke Conference (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
1. ISCHEMIC STROKE AND HYPERACUTE TREATMENT IN SEBERANG JAYA HOSPITAL: THE SEBERANG PRAI MODULE 2. ASSOCIATION OF ADMISSION BLOOD SUGAR LEVEL WITH ADMISSION NIHSS AND mRS 3 MONTHS POST ISCHEMIC STROKE THROMBOLYSIS: SEBERANG JAYA HOSPITAL 3. ASSOCIATION OF WEIGHT WITH ADMISSION STROKE SEVERITY AND FUNCTIONAL OUTCOME IN ACUTE ISCHEMIC STROKE PATIENTS WHO RECEIVED INTRAVENOUS THROMBOLYSIS IN SEBERANG JAYA HOSPITAL 4. ASSOCIATION OF SMOKING WITH ADMISSION STROKE SEVERITY, TYPES OF STROKE AND ISCHAEMIC STROKE SUBTYPES AMONG STROKE PATIENTS IN HOSPITAL SEBERANG JAYA 5. OUTCOME OF ISCHEMIC STROKE THROMBOLYSIS TREATMENT IN SEBERANG JAYA HOSPITAL, A SINGLE CENTER 10 YEARS REVIEW: 2012- 2021 6. A RARE COMPLICATION OF ACUTE ISCHEMIC STROKE DURING CARDIAC CATHETERIZATION: A CASE REPORT 7. STROKE AWARENESS AMONGST HEALTHCARE PROVIDERS IN AN UPPER MIDDLE-INCOME COUNTRY 8. HYPERCOAGULABLE STATE LEADING TO THROMBOTIC COMPLICATIONS AND CEREBRAL ARTERY INFARCTION IN PATIENT WITH SEVERE COVID-19 INFECTION: A CASE REPORT 9. LESSONS LEARNT FROM A POSTERIOR CIRCULATION STROKE IN A COVID-19 PATIENT: A CASE REPORT